FRAKSINASI PROTEIN KAPANG LAUT Xylaria psidii KT30 DAN SITOTOKSISITASNYA TERHADAP SEL HeLa [Fractionation of Proteins of Marine Fungus Xylaria psidii KT30 and their Cytotoxicity against HeLa Cells] - Mita Gebriella Inthe; Kustiariyah Tarman; Mega Safithri (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
FRAKSINASI PROTEIN KAPANG LAUT Xylaria psidii KT30 DAN SITOTOKSISITASNYA TERHADAP SEL HeLa[Fractionation of Proteins of Marine Fungus Xylaria psidii KT30 and their Cytotoxicity against HeLa Cells]Mita Gebriella Inthe1), Kustiariyah Tarman1)* dan Mega Safithri2)1) Departemen Teknologi Hasil Perairan, Fakultas Perikanan dan Ilmu Kelautan, Institut Pertanian Bogor, Bogor2) Departemen Biokimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Institut Pertanian Bogor, Bogor Diterima 22 Juli 2013 / Disetujui 03 Maret 2014ABSTRACT Cervical cancer is the most common cause of death for Indonesian women after human breast cancer. One of the efforts of cancer treatment is the utilization of natural compounds. One of the microorganisms having the potential as anticancer agent is endophytic fungi. Endophytic fungi from the marine habitat can be isolated from sea weeds, sea grasses, sponges, and mangroves. Xylaria psidii KT30, a marine fungus used in this study was isolated from red seaweed Kappaphycus alvarezii. Xylaria psidii KT30 was cultivated in potato dextrose broth medium for nine days at room temperature 27-29°C in shaking condition. This study aimed to obtain protein fractions from X. psidii KT30 and determine their toxicity againt Chang and HeLa cells. The fractionation process was conducted using DEAE Sephadex A-50 column chromatography and the toxicity was determined by Brine Shrimp Lethality Test (BSLT). The metabolites excreted in the culture broth was extracted using 90% of ammonium sulphate. The extract was then tested for their toxicity against HeLa and Chang cells by Microculture Tetrazolium Technique (MTT) assay.The results revealed that LC50 of the protein extract of X. psidii KT30 was 104.95 ppm and IC50 was 69.9 ppm. Based on the National Cancer Institute (NCI), this value showed moderate cytotoxicity against HeLa cells.